Implementasi Program Boarding School dalam Menumbuhkan Karakter Religius Siswa di SMP Negeri 1 Kebumen - Khotimah, Ayu Khusnul; Wi Hargina, Devi Yaniar (IAINU Kebumen, 2024)
Implementation of the Boarding school Program in Fostering Students' Religious Character at SMP Negeri 1 Kebumen. The research objectives are: (1) To find out the implementation of boarding school program in shaping students' religious character in SMP Negeri 1 Kebumen. (2) To find out the supporting factors and inhibiting factors in the implementation of the boarding school program in shaping students' religious character at SMP Negeri 1 Kebumen.This research uses a qualitative approach. The informants in this study were the principal, head of the boarding school, administrators, and boarding school students of SMP Negeri 1 Kebumen. This data collection technique uses interview, observation, and documentation techniques. The data analysis techniques used are data reduction, data presentation, data conclusion/verification. The results show that the implementation of the boarding school program is carried out according to predetermined provisions, covering the daily activities of students from waking up to sleeping again, with the aim of shaping religious character through religious, academic, and extracurricular activities. The methods used include general explanations, worship practices, and an emotional approach between teachers and students. Evaluation of the success of the program is done through assessment of discipline, worship, responsibility, and honesty of students. Supporting factors include adequate facilities and a conducive environment, while inhibiting factors include the moral crisis due to the use of cellphones and the lack of facilities and infrastructure.